Variability in the carbon isotope composition of individual amino acids in plant proteins from different sources: 1 Leaves - McCullagh, J; Kruger, N; Hedges, R; Lynch, A (Elsevier, 2016)
The natural carbon isotope composition of individual amino acids from plant leaf proteins has been measured to establish potential sources of variability. The plant leaves studied, taken from a range of plant groups (forbs, trees, grasses, and freshwater aquatic plants), showed no significant influence of either season or environment (water and light availability) on their δ13C values. Plant groups did, however, differ in carbon isotope composition, although no consistent differences were identified at the species level. A discriminant analysis model was constructed which allowed leaves from (1) nettles, (2) Pooideae, (3) other Poales, (4) trees and (5) freshwater higher plants to be distinguished from each other on the basis of their natural abundance 13C/12C ratios of individual amino acids. Differences in carbon isotope composition are known to be retained, to some extent, in the tissues of their consumers, and hence an understanding of compound-specific variation in 13C/12C fractional abundance in plants has the potential to provide dietary insights of value in archaeological and ecological studies.